PROGRAM ANIMASI INTERAKTIF PENGGOLONGAN HEWAN SEBAGAI MEDIA PEMBELAJARAN PADA SDN PENGASINAN IV BEKASI - Juarni Siregar; Sinta Rukiastiandari; Bayu Jayus Suwito (Universitas Sahid Surakarta, 2019)
Learning media always develops every year, one of which is animation. Basically animation is one form of entertainment, and by making learning media can make children, especially elementary school students, become more happy in learning. Learning methods used in elementary schools still use the lecture or face-to-face method to students, so it is necessary to add more interesting learning media. In the teaching process, the teacher only uses the media as a guide to teaching, especially the Science course, as a result students find it difficult to know clearly about the living costs, especially regarding the type of animal classification. In this study the authors took research material from the results of observations and interviews of several students in elementary schools, teachers and related parties. For this reason the author made the Animal Classification Interactive Animation Program as a Learning Media in Bekasi IV Elementary School of Elementary School became one of the solutions for elementary school students in learning the types of animal classification and simplifying and improving efficiency in the learning process.